Self-assembled capsules of poly-N-glycidyl histidine ether–tannic acid for inhibition of biofilm formation in urinary catheters1. Issue 85 (16th September 2015) - Mahata, Denial; Mandal, Santi M.; Basak, Amit; Nando, Golok B.
<x xml:space="preserve">Abstract</x> A coating made of N-glycidyl-histidine ether–tannic acid complex, a biocompatible polymer, onto a catheter surface inhibits the biofilm formation and helps to control the catheter associated infections caused by biofilm forming MDR pathogens.